2009
DOI: 10.1080/03009740902758875
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal DNA methylation in CD4+ T cells from patients with systemic lupus erythematosus, systemic sclerosis, and dermatomyositis

Abstract: Reduced DNA methylation and abnormal expression of methylation-related genes in CD4+ T cells are associated with SLE and SSc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
124
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 227 publications
(131 citation statements)
references
References 40 publications
6
124
1
Order By: Relevance
“…40 Global reductions in T-cell DNA methylation are correlated with the development of autoimmunity, including systemic lupus erythematosus, rheumatoid arthritis, systemic sclerosis, and dermatomyositis. 41,42 There are also murine models of systemic lupus erythematosus that are induced by use of Dnmt1 inhibitors, 43 but the current model is the first known example of aggressive autoimmunity arising from precise genetic targeting of a single Dnmt enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…40 Global reductions in T-cell DNA methylation are correlated with the development of autoimmunity, including systemic lupus erythematosus, rheumatoid arthritis, systemic sclerosis, and dermatomyositis. 41,42 There are also murine models of systemic lupus erythematosus that are induced by use of Dnmt1 inhibitors, 43 but the current model is the first known example of aggressive autoimmunity arising from precise genetic targeting of a single Dnmt enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…CD4+ T-cell DNA from patients with SSc is significantly hypomethylated relative to healthy controls, and the levels of DNMT1, MBD3, and MBD4 mRNAs are significantly decreased in SSc patients [19]. Furthermore, reduced expression of DNMT3a results in enhanced histone acetylation.…”
Section: Systemic Sclerosismentioning
confidence: 99%
“…Based on these genome-wide analyses, our studies have found that Tpaths and Tregs have different methylation density distribution in their autosomes and chromosome X. These novel results suggest epigenetic differences may contribute to the functional differentiation/specification of Tpaths vs. Tregs [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43].…”
Section: Both Foxp3mentioning
confidence: 93%